DETERMINANT FACTORS AFFECTING ON ACCURACY OF AUDITOR’S OPINION: MULTIGROUP ANALYSIS - Syahputra, Briyan Efflin; Irawati, Anggit Esti; Afnan, Akhmad; Ceisari, Btari Bunga (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2020)
The increasing number of cases of manipulation of financial statements that often occur to date has made the public increasingly question the performance of the auditor profession. This is because, most cases of manipulation can occur due to the negligence of auditors who are unable to detect the fraud. So the opinion published is not correct, and then the information presented in the auditor's report becomes misleading. Therefore, it is necessary to conduct research to determine the various factors that can increase the accuracy of auditor's opinion. This research was conducted with the aim of analyzing the relationship between auditor competence, experience, and professional skepticism on accuracy of auditor's opinion. In addition, this research was also conducted to analyze the moderating effect of the gender variable on the respective relationship between auditor competence, experience, and professional skepticism on accuracy of auditor's opinion. This research was conducted using a quantitative approach with a survey method through distributing questionnaires to 142 auditors who work in public accounting firms in Yogyakarta, Solo and Semarang. This research was tested statistically using simultaneous equations assisted by the SmartPLS application. This research result has found that auditor competence, experience and professional skepticism gives positive influence on accuracy of auditor's opinion. In addition, gender has also been shown to have a positive effect on accuracy of auditor’s opinion as moderating variable.